Cardiomyopathy as the first manifestation of Friedreich's ataxia - Rafael Tuzino Leite Neves Maffei; Giulio de los Santos Fortuna; Luca Campolino Rosso; Pedro Dragone Pires; Ivan Rondelli (University of São Paulo, 2021)
We present the case of a female patient diagnosed in childhood with Friedreich Ataxia (FA). At the age of 6, she developed left congestive heart failure with cardiomyopathy, as evident on echocardiogram. Neurologic signs only appeared at age 7, including marked loss of muscle mass, gait instability, muscle clonus, and Babinski's signal. At age 27, she had a stroke and was hospitalized; a few days later, she had a cardiorespiratory arrest with asystole, leading to death. The autopsy disclosed severe cardiomyopathy and significant myocardial replacement with fibrosis; therefore, the cause of death was assumed to be heart failure. Compared to the literature, our case has some unique features, such as cardiac disease as the presenting manifestation instead of gait instability, which is the major initial sign in most FA cases. Since our patient was submitted to an autopsy, it was an opportunity to retrieve important data to confirm the diagnosis and to evaluate the pathophysiology of this entity, such as myocardium fibrosis and cerebellar degeneration. In summary, our case demonstrates that cardiac disease can be the first manifestation of FA, with eventual diagnostic and prognostic implications. In addition, the autopsy provided findings of severe cardiomyopathy associated with FA.